Tathowwur Mafhum Al-Adab Al-‘Araby: Dirasah Lughawiyah Tarikhiyyah - Ilham Ramadhan; Haniah Haniah (Journal of Arabic Literature (JaLi), 2019)
Arabic literature has  other characteristics of world literature. Begins with the division of Arabic literature into historians and the concept of the meaning of "Adab al-‘Araby" varying from era to era. This simple writing will explain the different meanings of this field. Due to the pre-Islamic era, Arabic literature was a sense of food. The concept of literature in this era has been associated with banquet, meaning food that calls people to their food and performs this habit in the winter when the cold and the possibility of generosity to people. In the Islam era, the meaning of literature has changed to education and literature by the dakwah of Islam to people and its teachings and the refinement of souls. In the Umayyad era, the concept of literature became the meaning of education. In the Abbasid era literature was the sense of the call to Mahamad and Almkramm. In modern times came literature in the sense of the French (Litterature), which the French to write everything in the language.